Special features of the genre of the "Vita Plotini": who was Porphyry referring to? - Roman Soloviev (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
The article presents the analysis of genre dominants of "The Life of Plotinus" by Porphyry and analyses the polemical sources of the text. Having established the lack of research on the genre of the text in the modern bibliography, the author places the Life of Plotinus into the range of the late antique biographies, and determines the main characteristics of the analyzed text. The title of the text indicates Porphyry's dual purpose: to introduce the reader to the personality of Plotinus, whom Porphyry deliberately presents as theios aner, and also to present Plotinus' 54 treatises within the coherent system of the Enneads. The dual task is also reflected in the structure of the Life. Reconstructing the image of Porphyry in the text, the author of the article highlights the techniques that create the image of the author of Plotinus' Life. Emphasizing his own place in the hierarchy of the school is caused by the polemic both within the Neoplatonic school (with the earlier edition of Plotinus' treatises by Amelius; this is shown through the analysis of the introduction of the Life of Plotinus) and outside it. The author establishes the pragmatics of the key episodes of the text and shows that the text is built around a constructed hierarchy of testimonies: from the fellow student, Amelius, to the Oracle of Apollo. By highlighting the essential attributes of the hero of the biography, the author illustrates the dynamism of Porphyry's conception: Vita Plotini is not only an introduction to the edition, but also a didactic text, depicting a contemporary who has achieved the goal of human life. In the final part of the article, the author analyses the approaches to the identification of the opponents of Porphyry in the literature and sets forth his own hypothesis: the text was created in opposition to the school of Origen and to the image of the scholarch, which was drawn by Gregory the Wonderworker and Eusebius of Caesarea. The hypothesis of Porphyry's response to the Christian texts is grounded by the new lexical similarities with Origen.